The Golden Hour and Acute Brain Ischemia: Presenting Features and Lytic Therapy in Over 30,000 Patients Arriving Within 60 Minutes of Onset - Saver, Jeffrey L. (2010)
BACKGROUND: The benefit of intravenous thrombolytic therapy in acute brain ischemia is strongly time dependent. METHODS: The Get with the Guidelines-Stroke (GWTG-Stroke) database was analyzed to characterize ischemic stroke patients arriving to hospital Emergency Departments (EDs) within 60 minutes of last known well time from 4/1/2003-12/30/2007. RESULTS: During the 4.75 year study period, among 253,148 ischemic stroke patients arriving directly by ambulance or private vehicle to 905 hospital EDs, 106,924 (42.2%) had documented exact last known well times. Onset to door time was ≤ 60 minutes in 30,220 (28.3%), 61-180 minutes in 33,858 (31.7%), and >180 minutes in 42,846 (40.1%). Features most strongly distinguishing ≤ 60, 61-180, and > 180 minutes arriving patients were: greater stroke severity (median NIHSS 8.0 vs 6.0 vs 4.0, p <.0001) and more frequent arrival by ambulance (79.0%. vs 72.2% vs 55.0%, p <.0001). Compared with 61-180 minute arrivers, golden hour patients received IV thrombolytic therapy more frequently (27.1% vs 12.9%, OR 2.51, 95% CI 2.41-2.61, p <.0001), but door to needle time (DTN) was longer (mean 90.6 vs 76.7 minutes, p <.0001). DTN ≤ 60 minutes was achieved in 18.3% of golden hour patients. CONCLUSIONS: At GWTG-Stroke hospital EDs, more than one quarter of patients with documented onset time, and at least one eighth of all ischemic stroke patients, arrive within 1 hour of onset, where they receive thrombolytic therapy more frequently but more slowly than late arrivers. These findings support public health initiates to increase early presentation and shorten door to needle times in patients arriving within the “golden hour.”